Flowability and moldability of zirconia micro-part via micro-powder injection molding - Muhammad Mohamed Amin,; Norhamidi Muhamad,; Abu Bakar Sulong,; Al Basir,; Nur Aisyah Miza Ahmad Tamizi, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The micro-powder injection moulding process is a favourable process to produce micro-sized components of zirconia. The aim of this study is to study the flowability of zirconia feedstock and to ensure the moldability of micro-sized zirconia parts without any defects. To obtain the critical powder volume percentage (CPVP), zirconia was deposited inside a Brabender mixer while oil was added gradually with an interval of three minutes. The value of 2,3 and 4 vol.% less than CPVP was mixed with palm stearin and low-density polyethylene (LDPE) binders to produce three feedstocks and run through a rheometer to test the flowability of each feedstock. The feedstock with the best flowability characteristic was then subjected to micro-powder injection moulding process through trial and error to achieve the optimum parameters for micro-sized zirconia part without any defects. The CPVP of zirconia achieved for this study was 49.92 vol.% in which the optimal loadings of 46 vol.%, 47 vol.% and 48 vol.% feedstocks were analysed using the rheometer. The results show that 46 vol.% feedstock was most suitable for producing zirconia micro-part without any defects compared to other powder loadings due to its low viscosity, high shear thinning, flow behaviour index less than 1 and low activation energy. Injection moulded zirconia micro-sized green parts without any defects were produced using the following parameters: 10 bar of injection pressure, 70 °C of mould temperature, 190 °C of melt temperature and 7 seconds of injection time, respectively. Zirconia micro-sized green parts regularly exhibited short-shot defects when mould temperatures less than 70 °C were applied. The results showed that by employing feedstocks containing 46 vol.% of zirconia, micro-sized zirconia parts without any defects can be produced successfully through the micro-powder injection moulding process.